IDENTIFYING CHARACTER PRESENTATION AND MOTHERHOOD ISSUE THROUGH THE TECHNIQUE OF FOCALIZATION IN THE WITCH OF PORTOBELLO BY PAULO COELHO - Putriani, Rima (2014)
The present research entitled Identifying Character Presentation and Motherhood Issue through the Technique of Focalization in the Witch of Portobello by Paulo Coelho is a textual analysis on one of Paulo Coelho's novels focusing on the narrative perspective or focalization and motherhood issue inside the novel. The discussion focused on the main character in the story to reveal the character's traits and her motherhood portrayal through focalization technique. Therefore, the discussion was framed within the theories of narratology and focalization (e.g. Gennette, 1983 and Culler, 1997), and feminist motherhood (e.g. Rich, 1976 and Badinter, 1982). The research utilized a qualitative method particularly textual analysis. The result of the research showed that Athena, the main character in the novel, was presented to be a strong, independent woman with paranormal abilities who was brave enough to take dangerous risks and difficult paths to satisfy her curiosity. It was also revealed that Athena was described to portray the traditional myth of motherhood who loved her son and took care of him very well.